Mental health and conceptual confusion: a philosophy of language analysis - Moreno Garay, Javier (2026)
This article analyzes the general model of mental health underlying contemporary public policies, with the aim of identifying the philosophical assumptions that sustain it. The problem addressed lies in the fact that this model is grounded in Cartesian ontological dualism and in a progressive medicalization of human life, which generates linguistic entanglements that affect the theoretical and practical coherence of psychological interventions. Through a methodology of conceptual analysis, supported by contributions from the philosophy of language, particularly the critiques of dualism formulated by L. Wittgenstein and G. Ryle, the article examines the use of the concept of mental health and its alleged scientification. The development of the argument shows how this usage introduces conceptual confusions that, in the sphere of professional practice, distort the understanding of the non-physical dimension of human life and the practices associated with its care. Finally, the article proposes possible structural links between ontological dualism and the contemporary economic and political order, as well as the need to develop conceptual and disciplinary alternatives that avoid medical-biological reductionisms.